(untitled) (International journal of medical sciences, 2026)
Tumors of the facial skeleton represent a heterogeneous group of benign and malignant neoplasms affecting the maxillofacial region. Due to the anatomical complexity of the facial bones and their proximity to vital neurovascular structures, surgical management remains highly challenging. The present study aims to evaluate modern surgical approaches in the treatment of facial skeletal tumors, focusing on oncological radicality, functional preservation, aesthetic outcomes, and postoperative quality of life. A clinical-analytical investigation was conducted involving patients who underwent surgical treatment for benign and malignant tumors of the facial skeleton. Contemporary techniques including computer-assisted planning, endoscopic approaches, microvascular reconstruction, and multidisciplinary management were assessed. The findings indicate that integration of advanced imaging, 3D modeling, minimally invasive techniques, and reconstructive microsurgery significantly improves oncological safety and functional outcomes. The study confirms that individualized surgical strategies based on tumor type, stage, and anatomical localization are essential for optimal results.